Interactive Music Distance Education Platform Based on RBF Algorithm - He, Sujie (EAI Endorsed Transactions on Scalable Information Systems, 2023)
INTRODUCTION: Since the 21st century, Internet technology has been developing rapidly, and the field of education has gradually broken through the traditional offline teaching mode; utilizing the Internet mode for distance education to break the time and space constraints of education and music education is more restrictive on time and space. However, if distance education can be better utilized to promote the development of online music education, it will promote the development of music education.OBJECTIVES: This paper combines the past research results of the RBF algorithm, music education and distance education to study the construction of an interactive music distance education platform based on the RBF algorithm. The algorithm is used to improve the quality of the construction of the distance education platform, and the algorithm mainly optimizes the information dissemination path of distance education in the construction of the interactive music distance education platform and improves the reliability of the platform construction.METHODS: The RBF algorithm is used to optimize the construction of the platform, and the case method is used to study individual schools to detect the actual application of music distance education and to find the strengths and weaknesses of the interactive music distance education platform, and to improve the weaknesses to enhance the platform.RESULTS: The study found that constructing an interactive music distance education platform will not guarantee the quality of distance education; teachers and students can not quickly realize the effective communication between teachers and students, and some teachers can not better apply the distance education platform. However, there is still room for developing interactive music distance education platforms.CONCLUSION: The research of interactive music distance education platforms based on the RBF algorithm has a significant positive effect on the development of distance education, art distance education, music education and so on in China. Therefore, it is necessary to continuously improve music education by utilizing online teaching methods and teaching resources.
Keywords: interactive music; distance education; RBF Algorithm